-2(5x+2)=-3x+7

Simple and best practice solution for -2(5x+2)=-3x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5x+2)=-3x+7 equation:


Simplifying
-2(5x + 2) = -3x + 7

Reorder the terms:
-2(2 + 5x) = -3x + 7
(2 * -2 + 5x * -2) = -3x + 7
(-4 + -10x) = -3x + 7

Reorder the terms:
-4 + -10x = 7 + -3x

Solving
-4 + -10x = 7 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-4 + -10x + 3x = 7 + -3x + 3x

Combine like terms: -10x + 3x = -7x
-4 + -7x = 7 + -3x + 3x

Combine like terms: -3x + 3x = 0
-4 + -7x = 7 + 0
-4 + -7x = 7

Add '4' to each side of the equation.
-4 + 4 + -7x = 7 + 4

Combine like terms: -4 + 4 = 0
0 + -7x = 7 + 4
-7x = 7 + 4

Combine like terms: 7 + 4 = 11
-7x = 11

Divide each side by '-7'.
x = -1.571428571

Simplifying
x = -1.571428571

See similar equations:

| 12=6ax-4xb | | -25-(-15)= | | 3+y4=-y8 | | 10(12)=5(18) | | 47-6x=19+8x | | 7Z-3y=2 | | 6ax-4xb=12 | | N+(4.361)=59.78 | | -41=-3x-5 | | y=5.00+0.25x | | 9(x-1)+x=11 | | 6-9x=6x-9x-6 | | (x^2)+2x+40=(x^2)-x+190 | | 36r^2-1=0 | | 9y-8-6y+7=0 | | -25+55.5+(-29)= | | 6(-3x-3)=5x | | 7x+5x-54=72-6x | | 2c-58=7c-24 | | -15=5b+12-2b+b | | 3x+2+2x-1=6x-20 | | 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 | | -5+-16= | | 2b-8=0.4 | | (4x+7y)+(x-3y)= | | 5-2x=-5-x | | k+(4.21)=19.3 |

Equations solver categories